Investigation of the Effect of Titanium Doping on the Physical Properties of SnS Thin Films Prepared via Chemical Spray Pyrolysis - Hiba Saad Rasheed (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study systematically examined the effects of titanium (Ti) doping on the structural, morphological, and optical properties of SnS thin films prepared via chemical spray pyrolysis (CSP). X-ray diffraction (XRD) analysis confirmed that all films retained a polycrystalline orthorhombic structure, with the (021) plane remaining dominant regardless of Ti concentration (0, 2 and 4 at.%). Ti incorporation led to an increase in crystallite size from 16.22 nm for pure SnS to 23.61 nm at 4% Ti. Additionally, dislocation density decreased with doping, indicating fewer defects and potential improvements in charge carrier mobility. Atomic force microscopy (AFM) revealed that increasing Ti content reduced surface roughness from 7.75 nm to 4.21 nm and decreased particle size from 44.42 nm to 31.00 nm. Optically, Ti doping caused a slight narrowing of the bandgap from 1.65 eV to 1.55 eV. Transmittance decreased from 94% to 87%., while the extinction coefficient and refractive index also declined.
Keywords: SnS thin films; titanium doping; chemical spray pyrolysis; structural properties; optical band gap; surface morphology